Turnover Intention Review: The Influence Of Organizational Justice And The Work Environment - Sri Rahayu; Meilaty Finthariasari Finthariasari; Dinda Rafika Santri (UNIVED Press, 2022)
This research is based on the gap phenomenon encountered by researchers in the field. The purpose of the current study is to determine how much influence organizational justice and work environment have on turnover intention. This type of research is a quantitative research using a survey approach. In this study, data were collected through a questionnaire method with a sample of 356 respondents from private company employees in Bengkulu City. The results showed that organizational justice (x1) was proven to have a greater influence on turnover intention when compared to the work environment (x2), which were 22.2% and 12.4%, respectively, with a significant negative direction. The results of the regression analysis test are formulated with the equation Y = 10.480 - 0.222 (X1) - 0.124 (X2)